The Effect of Schoology Usage to the Students' Cognitive Performance - Ita Sarmita Samad; Sri Rosmiana; Umiyati Jabri (Edumaspul: Jurnal Pendidikan, 2020)
Technology has been growing explosively and give positive impact to the educational system. Universities are starting to apply such the online platform or blended learning to enhance their teaching quality. Yet, the teaching media used in STKIP Muhammadiyah Enrekang is still in conventional model. Thus in order to update the teaching media in this institutuion, this present study investigated the use of schoology as online platform in enhancing the students’ cognitive performance. The participants is the fourth semester students of English education program in academic year 2019/2020. The content is limited to the translation subject. The method is quantitative research design. The data was collected through essay test of translation and anlayzed using SPSS 25. The result shows that the tcounted is higher than ttable (6,926 > 1,833). Thus, it confirms that the use of schoology can enhance the students’ cognitive performance especially on the translation task.